Turning the Crisis Into an Opportunity: Digital Health Strategies Deployed During the COVID-19 Outbreak - Pérez Sust, Pol; Solans, Oscar; Fajardo, Joan Carles; Medina Peralta, Manuel; Rodenas, Pepi; Gabaldà, Jordi; Garcia Eroles, Luis; Comella, Adrià; Velasco Muñoz, César; Sallent Ribes, Josuè; Roma Monfa, Rosa; Piera-Jimenez, Jordi (JMIR Publications, 2020)
Digital health technologies offer significant opportunities to reshape current health care systems. From the adoption of electronic medical records to mobile health apps and other disruptive technologies, digital health solutions have promised a better quality of care at a more sustainable cost. However, the widescale adoption of these solutions is lagging behind. The most adverse scenarios often provide an opportunity to develop and test the capacity of digital health technologies to increase the efficiency of health care systems. Catalonia (Northeast Spain) is one of the most advanced regions in terms of digital health adoption across Europe. The region has a long tradition of health information exchange in the public health care sector and is currently implementing an ambitious digital health strategy. In this viewpoint, we discuss the crucial role digital health solutions play during the coronavirus disease (COVID-19) pandemic to support public health policies. We also report on the strategies currently deployed at scale during the outbreak in Catalonia.